Evaluación de las variables de desempeño cooperativo con enfoque en el buen vivir en la provincia de Esmeraldas - Tuárez Rendón, María Melania (2017)
In the present research, principles, dimensions, variables and indicators used in the evaluation of cooperative performance were reviewed and selected, which allowed to identify in a precise way the aspects that needed some type of improvement within the social performance of the cooperative since this one has been An aspect that until now has not been evaluated in depth in the country and less from the approach of Good Living. In order to achieve the proposed objectives, we applied methods such as the Delphi method and the Torgerson mathematical method. In addition, we applied the survey technique to collect information. The procedure was performed as follows: To the experts who would participate in the application of the Delphi method, the second one was consulted the indicators that allowed the evaluation of the social performance of the savings and credit cooperatives and production of the province of Esmeraldas; The analysis of the information obtained from the experts, the fourth tool was applied, the fifth was tabulated and analyzed the statistical data, sixth an improvement plan was made to correct the indicators that were not met in the cooperatives. The results obtained from the research show that 95% of the applied indicators are satisfactorily fulfilled within the savings and credit and production cooperatives of the province of Esmeraldas.